Heterozygous MAP3K20 variants cause ectodermal dysplasia, craniosynostosis, sensorineural hearing loss, and limb anomalies - Daniel Brooks; Elizabeth Burke; Sukyeong Lee; Tanya N. Eble; Melanie O’Leary; Ikeoluwa Osei-Owusu; Heidi L. Rehm; Shweta U. Dhar; Lisa Emrick; David Bick; Michelle Nehrebecky; Ellen Macnamara; et al. (Human Genetics, 2024)

Loss of Neuron Navigator 2 Impairs Brain and Cerebellar Development - Andrea Accogli; Shenzhao Lu; Ilaria Musante; Paolo Scudieri; Jill A. Rosenfeld; Mariasavina Severino; Simona Baldassari; Michele Iacomino; Antonella Riva; Ganna Balagura; Gianluca Piccolo; Carlo Minetti; et al. (The Cerebellum, 2022)
Cerebellar hypoplasia and dysplasia encompass a group of clinically and genetically heterogeneous disorders frequently associated with neurodevelopmental impairment. The Neuron Navigator 2 ( NAV2 ) gene (MIM: 607,026) encodes a member of the Neuron Navigator protein family, widely expressed within the central nervous system (CNS), and particularly abundant in the developing cerebellum. Evidence across different species supports a pivotal function of NAV2 in cytoskeletal dynamics and neurite outgrowth. Specifically, deficiency of Nav2 in mice leads to cerebellar hypoplasia with abnormal foliation due to impaired axonal outgrowth. However, little is known about the involvement of the NAV2 gene in human disease phenotypes. In this study, we identified a female affected with neurodevelopmental impairment and a complex brain and cardiac malformations in which clinical exome sequencing led to the identification of NAV2 biallelic truncating variants. Through protein expression analysis and cell migration assay in patient-derived fibroblasts, we provide evidence linking NAV2 deficiency to cellular migration deficits. In model organisms, the overall CNS histopathology of the Nav2 hypomorphic mouse revealed developmental anomalies including cerebellar hypoplasia and dysplasia, corpus callosum hypo-dysgenesis, and agenesis of the olfactory bulbs. Lastly, we show that the NAV2 ortholog in Drosophila , sickie ( sick ) is widely expressed in the fly brain, and sick mutants are mostly lethal with surviving escapers showing neurobehavioral phenotypes. In summary, our results unveil a novel human neurodevelopmental disorder due to genetic loss of NAV2 , highlighting a critical conserved role of the NAV2 gene in brain and cerebellar development across species.